Strategi Branding dalam Meningkatkan Daya Tarik Produk di Pondok Pesantren - Faradila, Selma; Suwaidi, Rahman Amrullah (Journal Of Human And Education (JAHE), 2024)
The community service carried out at the Tahfidzul Qur'an Al-Itqon Islamic Boarding School in Jombang focuses on developing students' skills in the production, branding and marketing of products based on raw materials that are easily available in the local market, especially shredded cob. This activity aims to overcome several main problems faced by Islamic boarding schools, including limited knowledge and skills of students in aspects of processed food production and marketing, as well as a lack of product innovation which affects competitiveness in the market. By utilizing the potential of human resources and existing facilities, this program is designed to increase the economic independence of Islamic boarding schools and equip students with skills relevant to the needs of the modern job market. This service includes a series of practical and theoretical training. Students are taught about hygienic and innovative shredded production techniques, branding development through creating attractive logos and packaging designs, as well as effective digital marketing strategies using platforms such as Shopee. This activity also involves direct assistance in marketing to build a wider distribution network. The results of this service are very significant. Santri not only gain increased skills in shredded cob production, but also in branding and marketing aspects. This initiative has succeeded in increasing sales of Islamic boarding school products, which not only supports the Islamic boarding school's economic independence but also provides a sustainable business model.